#TITLE_ALTERNATIVE# - (NIM : 324 02 001); Pembimbing 1: Dr.Gunawan Ibrahim; Pembimbing 2: Prof. Dr. Sri Widiyantor, Wandono
The Toba caldera complex is one of the largest Quaternary calderas in the world. The area known as the Batak tumor was controlled by a unique interaction between the Eurasian continental plate and the Indo-Australian oceanic plate. The Toba region lies at the uplifted continental crust of SE Asia, oblique subduction, and along the northern part of the great Sumatran fault. The unique geological setting of this area has motivated many researchers (geologists and geophysicists) to explore information about the caldera complex which is about 74.000 years of age.